2007
DOI: 10.1111/j.1530-0277.2006.00315.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use in Pregnant and Nonpregnant Russian Women

Abstract: Pregnant and nonpregnant Russian women were willing to answer detailed questions about their drinking behavior. Although most pregnant women studied reduced their drinking during pregnancy, one-third of the pregnant women did not stop drinking. It is important to find out what enabled two-thirds of the pregnant women to stop drinking before or during their pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
1
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 20 publications
3
44
1
6
Order By: Relevance
“…In Russia, 899 women were interviewed about their alcohol consumption habits and their findings showed that nearly all pregnant women drank during the year before they became pregnant; of these, 60% reported drinking when they knew they were pregnant, and 34.9% drank in the 30 days before the interview (Kristjanson, Wilsnack, Zvartau, Tsoy, & Novikov, 2007). Knowing the high level of alcohol consumption by pregnant women in Russia, the higher risk of some difficulties during their children's development is assumed, including more hyperactivity and attention problems.…”
Section: Discussionmentioning
confidence: 99%
“…In Russia, 899 women were interviewed about their alcohol consumption habits and their findings showed that nearly all pregnant women drank during the year before they became pregnant; of these, 60% reported drinking when they knew they were pregnant, and 34.9% drank in the 30 days before the interview (Kristjanson, Wilsnack, Zvartau, Tsoy, & Novikov, 2007). Knowing the high level of alcohol consumption by pregnant women in Russia, the higher risk of some difficulties during their children's development is assumed, including more hyperactivity and attention problems.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in Russia and Ukraine, the rates of monthly heavy episodic or heavy alcohol use vary from 31% to 82% for men and from 1% to 11% for women (Bobak et al, 1999(Bobak et al, , 2004Malyutina et al, 2001;Pakriev et al, 1998;Webb et al, 2005). Two recent surveys conducted in Russia estimated the prevalence of any alcohol consumption among pregnant women to be as high as 25.5%-60%; however, results should be generalized with caution (Grjibovski et al, 2002;Kristjanson et al, 2007). Prior research also indicates that women in post-Soviet societies experience a much greater level of psychosocial distress than men, although at least one study suggests that such elevated stress levels do not translate to risky alcohol consumption patterns in women (Cockerham et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Recent figures show that many women consume alcohol during pregnancy in developed countries; for example, it has been reported that 30% of American women (19), 59% of Australian women (15), and 30 -60% of European women (13,16,21,26,35,38) drink alcohol at some stage during their pregnancy. Prenatal exposure to ethanol can result in the fetal alcohol syndrome (FAS) or fetal alcohol spectrum disorders (FASD), which are characterized by growth restriction, brain dysmorphology and dysfunction, in addition to craniofacial anomalies in the case of FAS (31,34).…”
mentioning
confidence: 99%